(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article deals with the problems of manipulating mass consciousness, carried out through the actualization of fear as a basic human emotion, examines the specificity of verbal apocalyptic paintings in political advertising.